Epigenetic Mechanisms Contribute to Evolutionary Adaptation of Gene Network Activity under Environmental Selection - Luo, Xinyue (Cell Rep, 2020)
How evolution can be facilitated by epigenetic mechanisms has received refreshed attention recently. To explore the role epigenetic inheritance plays in evolution, we subject isogenic wild-type yeast cells expressing P(GAL1)-YFP (yellow fluorescent protein) to selection by daily sorting based on reporter expression. We observe expression-level reductions in multiple replicates sorted for the lowest expression that persist for several days, even after lifting the selection pressure. Reduced expression is due to factors in the galactose (GAL) network rather than global factors. Results using a constitutively active GAL network are in overall agreement with findings with the wild-type network. We find that the local chromatin environment of the reporter has a significant effect on the observed phenotype. Genome sequencing, chromatin immunoprecipitation (ChIP)-qPCR, and sporulation analysis provide further insights into the epigenetic and genetic contributors to the expression changes observed. Our work provides a comprehensive example of the role played by epigenetic mechanisms on gene network evolution.